Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Peserta Didik Kelas V SD pada Materi Keliling Bangun Datar - Zahra, Fatimah; Masniladevi, Masniladevi; Andika, Refiona; Ningsih, Yarisda (Lembaga Yasin AlSys, 2025)
The low academic performance of students in mathematics serves as the primary motivation for this study, indicating that conventional teaching methods have not yet succeeded in fostering effective learning processes. The aim of this research is to analyze the effect of the Problem-Based Learning (PBL) model on students' learning outcomes in the topic of perimeter of plane figures. A quantitative approach was employed using a one-group pretest–posttest experimental design. The sample consisted of fifth-grade students (class VB) selected through cluster sampling as part of probability sampling. The results show an improvement in learning outcomes following the implementation of the PBL model, as evidenced by an increase in average scores from 29.86 (pretest) to 72.71 (posttest). A statistical test using the Mann-Whitney method yielded a significance value of 0.002 (p < 0.05), indicating a significant effect of the PBL model on student learning outcomes. It can therefore be concluded that the application of the PBL model contributes positively to enhancing students' conceptual understanding of mathematics, particularly in the topic of perimeter of plane figures, and can be implemented regularly to foster more meaningful learning experiences.